Mental health in Jamaica : a descriptive study - Harris, Michelle (2003)
Presents a brief history of mental health care in Jamaica, contextualizes research on the distribution of mental health and highlights areas for future investigation. Utilizes quantitative data from a study of Jamaican adults to help one to understand some of the ways in which social factors may relate to psychological distress and well-being.